Health risk assessment of heavy metals in indoor dust from Bushehr, Iran - Saeed Ardashiri; Seyed Enayat Hashemi (Iranian Journal of Health, Safety and Environment, 2018)
Environmental contamination with heavy metals is one of the main concerns on a global scale and the risk related to exposure to heavy metals present in indoor dust is considered as a serious threat to human health. Therefore, the purpose of the current research was to evaluate the heavy metals concentrations in indoor dust and their potential risks in urban areas in Bushehr city, Iran. Fifty-four indoor dust samples were collected from different buildings including lab rooms, offices, school rooms and households within the Bushehr City, during May - July 2016 and analyzed using ICP-AES (Arcousmodel, Germany). The sum of hazard quotient (hazard quotient (HQs) for heavy metals for adults declined in the order of Cr > Cd > Cu >Ni > Zn > Pb for the household while the order of ΣHQ for trace metals for adults in offices is Cr > Cd > Ni >Cu > Zn > Pb. Moreover, the values ΣHQ for trace metals for children declined in the order of Cr > Cd > Zn > Ni > Cu > Pb for the schools while the order of ΣHQ for trace metals for children in households is Cd > Zn >Cu > Cd > Ni > Cr > Pb. For all heavy metals, the HQs was about an order of magnitude higher for children than for adults. These findings can be attributed to the more vulnerability of children to the toxic substances.